Commonly Encountered Online EFL Learning from the Perspective of Students at PSDKU MBD - Lewier, Christian Albert; Meyer, Fredy (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2024)
The purpose of this study is to explore students' perception on problems and issues they encountered during the implementation of online learning. Students who live in remote areas at PSDKU MBD UNPATTI were frequently subject to unprecedented hardship in online study. This study employed qualitative descriptive research design where the data was collected through interview, observation and documentation. The result show that although they enjoyed online learning, these students expressed some challenges they faced in online teaching and learning process. The challenges were ranged from infrastructure to digital literacy. They stated that infrastructure factor has been the greatest challenge in their online learning activities. Lack of opportunities to interact with their lecturers have caused ineffectiveness in knowledge gain. These students also sounded the urgent needs for capacity building in regards to technology and digital literacy. These EFL learners are also facing the daunting dual task of learning the material while sharpening their digital capacity. The students who predominantly come from diverse remote areas in Southwest Maluku region are known to be less fortunate as compared to their counterpart students in main campus in Ambon city who have better teaching and learning facilities. Implication borne in the study will be further discussed in this study.